Theorising welfare state development : a case study of social insurance in the Republic of Ireland - Carey, Sophia (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2003)
This thesis has attempted to account for the development of social insurance in post-war Ireland by providing a theoretically informed analysis of the genesis of, and outcomes in, the 1952 Social Welfare Act. It begins with an overview of the main theoretical perspectives on the development of contemporary welfare states, highlighting the shifting concerns with similarity and difference that have informed research over the previous three or so decades. As the thesis moves on to suggest, much of the standard literature is somewhat problematic from an Irish perspective, and the ‘state of the art’ of contemporary Irish theorising reveals that there are many unanswered questions about the central determinants of the Irish welfare state. This reflects the very limited amount of research focused on locating Ireland in the now extensive literature on modem welfare states. This thesis has attempted to contribute towards filling this gap by assessing the extent to which diverse theoretical perspectives provide useful insights in accounting for the specific outcomes in one particular policy sector.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin